Implications of the lack of desiccation tolerance in recalcitrant seeds - Berjak, Patricia; Pammenter, Norman (Frontiers in Plant Science, 2013)
A suite of interacting processes and mechanisms enables tolerance of desiccation and storage (conservation) of orthodox seeds in the dry state. While this is a long-term option under optimised conditions, dry orthodox seeds are not immortal, with life spans having been characterised as short, intermediate and long. Factors facilitating desiccation tolerance are metabolic ‘switch-off’ and intracellular dedifferentiation. Recalcitrant seeds lack these mechanisms, contributing significantly to their desiccation sensitivity. Consequently, recalcitrant seeds, which are shed at high water contents, can be stored only in the short-term, under conditions not allowing dehydration. The periods of such hydrated storage are constrained by germination that occurs without the need for extraneous water, and the proliferation of seed-associated fungi. Cryopreservation is viewed as the only option for long-term conservation of the germplasm of recalcitrant-seeded species. This is not easily achieved, as each of the necessary procedures imposes oxidative damage. Intact recalcitrant seeds cannot be cryopreserved, the common practice being to use excised embryos or embryonic axes as explants. Dehydration is a necessary procedure prior to exposure to cryogenic temperatures, but this is associated with metabolism-linked injury mediated by uncontrolled ROS generation and failing anti-oxidant systems. While the extent to which this occurs can be curtailed by maximising drying rate (flash drying) it cannot be completely obviated. Explant cooling for, and rewarming after, cryostorage must necessarily be rapid, to avoid ice crystallisation. The ramifications of desiccation sensitivity are discussed, as are problems involved in cryostorage, particularly those accompanying dehydration and damage consequent upon ice crystallisation. While desiccation sensitivity is a ‘fact’ of seed recalcitrance, resolutions of the difficulties involved germplasm conservation are possible as discussed.